Grafia não convencional em textos escritos do 6º e 7º ano do Ensino Fundamental: proposta de atividades complementares ao livro didático - Silva, Elizandra Candido da (2021)
This Master thesis reports a research carried out with the aim to develop activities for teaching spelling to complement the textbook approach based on cases of unconventional spelling observed in written texts by students from the 6th and 7th grades of Elementary School. The analysis of data collected for diagnosis indicated the occurrence of spelling errors in the students’ texts, resulting from both the interference of phonological rules of Portuguese – vocalization, diphthongization and monophthongization – and the arbitrary nature of the writing conventions system – the graphical representation of the phonemes /s/, /z/ and /ʃ/ and nasalization represented by m and n, with greater recurrence of the first two cases. Based on the collected data, we conducted a bibliographic review on topics regarding the relationship between oral and written language (BORTONI-RICARDO, 2004; BORTONI-RICARDO, GONDIM; BENÍCIO, 2010; CAGLIARI, 2001; TEIS-ADAMANTE, 2020), the spelling of Portuguese (ALMEIDA, 2005; ARAGÃO, 2000; BATTISTI; MORAIS, 2016; BECHARA, 2009; BISOL, 2010; CAGLIARI, 2009; FARACO, 2012; MACHADO, 2012) and the teaching of writing and spelling (LEMLE, 2009; OLIVEIRA, 2005; CORRÊA, 2010; KOCH; ELIAS, 2017; MORAIS, 2003; MORAIS; SILVA, 2007; NÓBREGA, 2013; ROBERTO, 2016). We also carried out an analysis of the textbook used in the mentioned groups of students to verify how the topics related to spelling are addressed in the material, in order to guide the needs for complementing the material, based on the priorities revealed in the students’ texts. As a result, we developed five sets of activities to work with the main problems verified in the texts. It is, therefore, a qualitative, interpretive, propositional research. The study, conceived as action research, with the perspective of intervention in the classroom, was reformulated due to the Covid-19 pandemic, as school activities took place remotely during the period that would be intended for the application of the activities. Nevertheless, because it offers a proposal for pedagogical intervention, this study still corresponds to the profile of research in Profletras, which is to offer theoretical and methodological contributions to the teaching of Portuguese, especially in the reading-writing axis.